EFL Learners’ Preferences and Emotions about Oral Corrective Feedback at Secondary Education in Turkey: Are There Gender and Grade-level Differences? - Yak???k, Burçak Y?lmaz (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
Oral corrective feedback has attracted the attention of EFL teachers and researchers in recent decades. The current study aims to investigate EFL learners’ preferences and emotions about oral corrective feedback with a specific focus on gender and grade level at secondary education in Turkey. Quantitative research methods were used to reveal the findings. 664 EFL learners participated in the study at two different state high schools in Ankara, Turkey. Mann-Whitney U and Kruskal-Wallis tests were used to investigate the OCF preferences of EFL high school learners. It was revealed that more than half of the high school EFL learners worried about making mistakes in the classroom; however, the majority of the learners agreed on the necessity of receiving OCF and they had positive feelings for being given immediate feedback by their teachers. Regardless of gender and grade level, EFL learners had a higher preference for ‘self-correction’. Females preferred ‘metalinguistic clues’ as the first choice and ‘peer correction’ as the last choice among the OCF types whereas males prefer ‘peer correction’ as the first, but ‘metalinguistic clues’ as the last choice. Among the grade levels, 10th-grade level learners have more concerns about making mistakes and these learners prefer ‘clarification request’ and ‘repetition of error’ a lot more than the 9th-grade level learners.